IFPRI Malawi maize market report, October 2024 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The Monthly Maize Market Report was developed by researchers at IFPRI Malawi to provide clear and accurate information on the variation of maize prices in selected markets throughout Malawi. All prices are reported in Malawi Kwacha (K). Highlights • Retail prices of maize increased by 4 percent in October. • Maize prices were lowest in the Northern region and highest in the Southern region. • ADMARC sales were reported in 5 of the 26 markets monitored by IFPRI. • ADMARC purchases were reported in 4 markets. • Retail prices of maize in Malawi were lower than most neighboring countries at the market exchange rate.